THE EFFECT OF THE SOWING PERIOD ON THE FORMATION OF PROTEIN IN THE MASH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article analyzes the changes in the field of mung bean at different times and the results of the study of the formation of protein in mung bean.